The dynamic oscillatory rheological properties of hen’s egg white proteins using various enzymes - Muhammed Yuceer (Acta Scientiarum. Animal Sciences, 2025)
This study evaluated the effect of different commercial enzymes on the rheological behavior of the treated hen’s egg white protein (HEWP). The enzymes of phospholipase A2, lipase, and protease were used in the research. These research findings indicate that all treated and non-treated HEWP samples exhibited non-newtonian behavior. It was observed that enzyme-hydrolyzed HEWP flow behavior was similar to that of the control HEWP samples where viscosity decreased with an increase in the shear rate. The lower storage modulus was obtained by phospholipase A2 and protease-treated samples. The protease enzyme treatment leads to a decrease in viscous modulus and an increase in storage modulus values.  The overall observation confirmed that the HEWP loses its liquidity after 64°C.